DEVELOPMENT OF TOOTHPASTE FORMULATION MODEL OF MANALAGI APPLE PEEL EXTRACT (Malus Sylvetris) WITH DIFFERENT CONCENTRATIONS AGAINST THE GROWTH OF STREPTOCOCCUS BACTERIA MUTANS IN VITRO AND IN VIVO - Risman Abdi Rapiuddin; Diyah Fatmasari; Arwani (Syntax Corporation Indonesia, 2023)
Background: Caries is a disease caused by damage to the enamel layer that can extend to the nerve part of the tooth. One way to prevent caries is to brush your teeth regularly using antibacterial herbal toothpaste that can reduce the number of colonies of streptococcus mutans bacteria. Apple peel is a useful herbal ingredient as an antibacterial, antioxidant, antifungal and antiproliferative, and polyphenolic compound. Objective: To determine the effect of developing a toothpaste formulation model of manalagi apple peel extract (malus sylvetris) with different concentrations on the growth of mutant Streptococcus bacteria in vitro and in vivo. Method: This study is a true experimental research using pre test and post test approach with control group design. Sampling was carried out using a simple random sampling technique and 15 respondents were obtained. This study was carried out for 3 days, where on the first day measurements were carried out (pretest) by taking saliva samples on respondents before brushing their teeth in the morning, and on the third day (posttest) measurements of respondents' saliva were carried out to test the bacterial colonies contained therein. Statistical analysis of Pre-Test Post-Test difference test using Paired T-Test difference test and One-Way Annova Test and Comparison Analysis with Post Hoc Tukey test. Results: This study showed that the dose of toothpaste in vitro testing was obtained the optimal dose, namely at the concentration of apple peel extract manalagi 25%, then in vivo tests the toothpaste formulation model of Manalagi apple peel extract (Malus Sylvetris) with the optimal dose (25%) was effective in inhibiting the growth of streptococcus mutans bacteria in vivo with an average decrease of -3.30 x 106 CFU / ml, with p value (0.005 < 0.05). control group + was -0.38 x 106 CFU/ml, and non-herbal toothpaste in control group - was -0.68 x 106 CFU/ml, but results Statistical analysis showed no significant difference in results before and after treatment in control group + (p value = 0.553 > 0.05) and control - (p value = 0.403 > 0.05). Conclusion: Manalagi apple peel extract toothpaste formulation model (malus sylvetris) with a concentration of 25% effective in inhibiting the growth of mutant Streptococcus bacteria in vitro and in vivo